THE ROLE OF INNOVATIVE ACCOUNTING IN ENCOURAGING BANK CREDIT AND PROVIDING FINANCIAL LIQUIDITY IN IRAQI BANKS - Abdul-Jabbar Alwan; Prof. Hayder Abbas AL-attar; Sajad Amer Diab Al-Zubaid (Scholar Express Journals, 2022)
The research aims to know the role that innovative accounting plays in activating and developing credit policy in Iraqi banks in order to encourage savings and provide liquidity, as this was achieved through analyzing spending operations on innovative accounting tools from electronic devices and information networks, as well as conducting analysis to measure bank credit. And knowing the volume of savings and liquidity in a sample of Iraqi banks listed in the stock market for the fiscal period (2018-2019-2020), and through this analysis, the research hypothesis was tested and its objectives were achieved. The most important finding of the research is that the application of innovative accounting tools by Iraqi banks contributes to reducing financial risks by providing appropriate mechanisms to complete the required work as quickly and accurately as possible, as well as a discrepancy in the rates of application of innovative accounting mechanisms among Iraqi banks as a result of the disparity between the possibilities available to them in Application, as most banks suffer from not keeping pace with the development taking place in international external banks. The most important thing recommended by the research is the need to activate the foundations of innovative accounting through the issuance of governance rules that banks apply by forming a governance committee in which several ministries and regulatory bodies participate, as well as the involvement of the auditing and control profession council for the purpose of organizing the work of banks and the need to make amendments to Some laws, regulations, and instructions in line with innovative accounting and its tools, such as the banking law, the financial markets law, the unified accounting system and the instructions attached to it
Keywords: Innovative accounting; bank credit; financial liquidity